2021
DOI: 10.9782/2331-4001-24.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Including Children with Disabilities in Egyptian Schools

Abstract: This study set out to investigate teachers' perceptions of barriers to including children with disabilities in general schools in Egypt. This descriptive, qualitative study drew on a purposive sample of twelve general and special education teachers within two educational districts in Cairo, Egypt. Through in-depth interviews, teachers were asked about their perceptions of the barriers that hinder the implementation of inclusive education in Egypt. Four categories of barriers were identified: structural-organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…[ 37 , 38 , 39 , 40 , 41 ]. However, in geographical areas that present cultural and educational differences with respect to Spain, such as Arabian regions, most teachers show a negative attitude towards it, possibly due to the lack of teacher training on inclusion and diversity through well-designed specific courses, poorly prepared school environment, inadequate curriculum and evaluation modules, among other barriers [ 42 , 43 , 44 , 45 ]. In contrast, other research in the Arab population shows that primary school teachers have a better perception of their skills with respect to inclusive education [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 , 38 , 39 , 40 , 41 ]. However, in geographical areas that present cultural and educational differences with respect to Spain, such as Arabian regions, most teachers show a negative attitude towards it, possibly due to the lack of teacher training on inclusion and diversity through well-designed specific courses, poorly prepared school environment, inadequate curriculum and evaluation modules, among other barriers [ 42 , 43 , 44 , 45 ]. In contrast, other research in the Arab population shows that primary school teachers have a better perception of their skills with respect to inclusive education [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Flower et al (2017), indicated that many pre-service teachers do not receive important content necessary for the success of students and teachers especially on how to use technology for their lessons with students. They are viewed as often feeling less prepared to deal with diversity in their classrooms due to the lack of useful skills in integrating technology into their lessons (Hassanein et al, 2021). Acknowledging the usefulness for teachers to be able to integrate technology into their lessons, the current curriculum includes a technology training component which considers how content, pedagogy, and technology dynamically constrain each other, helping teachers to utilise technology in classrooms more effectively (Nasr, 2020).…”
Section: Ineffective Technology Training Programs For Pre-service Tea...mentioning
confidence: 99%
“…The implementation of inclusive education is only possible when schools are designed and managed so that all children experience a quality learning environment, as a result of which a significant effort to reform the education system of most countries is required (Hassanein, Adawi, & Johnson, 2021).…”
Section: Recommendationsmentioning
confidence: 99%
“…During the last three decades, there has been a remarkable action oriented towards inclusive education, globally (Hassanein, Alshaboul, & Ibrahim, 2021). Many countries around the world are committed to providing education to all children without discrimination by signing conventions on the rights of the child and the rights of persons with disabilities (Hassanein, Adawi, & Johnson, 2021). Besides, the participation of all individuals, regardless of their strengths or weaknesses, is an inalienable right of human existence (Polyzopoulou & Tsakiridou, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation